The influence of pronunciation learning strategies on mastering English vowels - Rokoszewska, Katarzyna (Studies in Second Language Learning and Teaching, 2012)
The present paper focuses on the role of strategies in learning the pronunciation of the target language. First, an outline of various general classifications of language learning strategies is provided. Next, pronunciation learning strategies are defined and their various taxonomies are presented. This is followed by the description of the study which investigated the influence of pronunciation learning strategies on the perception and production of English pure vowels and diphthongs by first-year students of an English department. The results of the study indicate that students of English, who on average use pronunciation learning strategies rather occasionally, should receive some strategy-based instruction as there exists a significant relationship between the investigated phenomena, especially between the use of pronunciation learning strategies and the production of English monophthongs and diphthongs.